The Effectiveness Of Monopoly Educational Game Media On Students' Science Learning Outcomes - Firenita Agustin; Mahluddin Mahluddin; Andi Nurhasanah (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
The low learning outcomes of fourth-grade students in Natural and Social Sciences (IPAS) at Madrasah Ibtidaiyah Nurul Hidayah, Jambi City, became the focus of this study. This issue was caused by teacher-centered learning, the dominance of lecture methods, and the lack of engaging learning media. This study aimed to improve students’ learning outcomes through the implementation of monopoly-based learning media. The research employed Classroom Action Research (CAR) based on the Kemmis and McTaggart model, conducted in two cycles consisting of planning, action, observation, and reflection stages. The subjects were fourth-grade students. Data were collected through observation, tests, and documentation. The results showed an improvement in students’ learning outcomes in each cycle, with the average score increasing from 42.41 in the pre-cycle to 71.93 in Cycle I and 81.61 in Cycle II, with a learning completeness rate of 80.64%. These findings indicate that monopolybased learning media is effective in improving students’ learning outcomes in IPAS.